Ingressos em circulação: um estudo sobre a revenda, legislação e o papel das plataformas digitais - Teixeira, Izabela Martins; Salzedas, Rafael Peres (Universidade Federal de São Carlos, 2024)
This study carries out a survey on the resale of tickets, the legislation regarding the subject, what is scalping, analyzes platforms and, from a questionnaire, with 168 respondents, the behavior of the attending public towards the circulation of income and scams. The research examines the motivations of a resale, its legality, on which platforms we can find them and, from there, discuss and verify the problems surrounding the subject, the late existence of legislation on the exchange, scams applied through social networks and how this affects the public and the event production. Through a bibliographic survey, we can analyze the existing legislation, the Fan Statute and the consumer protection code, as well as as the recent approval of Law 14,597/23, which criminalizes exchange. It is through resells that fans can get tickets that are already sold out on official platforms, if They connect to each other and you can find the same ticket at different prices, but They encounter scams, abusive prices and are not protected by the event producer. oh Study indicates that greater regulation and policy implementation is necessary. audiences on the subject, as well as an improvement in purchasing and sales and social networks, in order to promote an enriching and safer experience for fans and those involved in the event.
Tickets in circulation: a study on resale, legislation and the role of digital platforms
Keywords: Venda e revenda de ingressos; Resale of tickets; Cambismo; Scalping; Golpes; Scams; Plataforma de ingressos; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::MERCADOLOGIA